Are there distinct dimensions of apathy? The argument for reappraisal. (April 2022) - Dickson, Shannon S.; Husain, Masud
Abstract: Apathy is widely accepted to be a multidimensional syndrome. Assessment scales typically probe one or more dimensions but there is no consensus on the precise nature of these domains. Existing major theoretical frameworks include cognitive, behavioural, and emotional dimensions of apathy. While a social domain has also been suggested, it is far less well studied. Here we argue that although most assessment scales have been developed with these theoretical frameworks in mind, few findings actually support the existence of some of the dimensions that have been proposed, with the evidence for separation of cognitive and behavioural dimensions particularly lacking. In our opinion, although there is evidence for behavioural and emotional domains of apathy, the contention that there might be a separate dimension of cognitive or executive apathy is far less robust. Further, while there is some evidence for a social dimension of apathy, this has not been investigated sufficiently to make any definitive conclusion. We argue that there is a pressing need to reconsider different domains of apathy using robust analyses of proposed theoretical dimensions.